Clinical and analytical performance of the BD Onclarity™ HPV assay for detection of CIN2+ lesions on SurePath samples - Ejegod, Ditte Møller (Papillomavirus Res, 2016)
BACKGROUND: The novel BD Onclarity(TM) HPV assay (Onclarity) on the BD Viper™ LT system (BD Diagnostics, Sparks, MD), detects E6/E7 DNA from 13 high-risk HPV genotypes and HPV66. We compared the analytical and clinical performance of the Onclarity Assay to that of Hybrid Capture 2 and LINEAR ARRAY using adjudicated histological outcomes from Danish women referred for colposcopy. METHODS: 276 women from Copenhagen, Denmark were referred for colposcopy with abnormal cytology and/or a positive HPV test. Two samples for HPV analysis were taken in BD SurePath™ and in the BD cervical brush diluent (CBD) media. ClinicalTrial gov. identifier: NCT01671462, Ethical Approval: H-4-2012-070. RESULTS: Histology was normal in 84 (31%) women, 70 (26%) had CIN1, 47 (17%) CIN2, and 68 (25%) had CIN3. The Onclarity assay detected 67 out of 68 (99%) ≥CIN3 and 113/115 (98%) ≥CIN2. The specificities for <CIN2 were 21%, 17%, and 22%, for HC2, Onclarity and LA, respectively. CONCLUSION: Overall, the Onclarity HPV assay performed well on SurePath LBC and CBD media, with clinical sensitivity and specificity matching those of HC2 and LA.